MANAGING MAXILLARY BONE LOSS USING GROWTH FACTORS IN PRE-IMPLANT THERAPY - Cardas Adelina; Stratan Ion; Moraru Daliana; Tibeica Andreea; Agop-Forna Doriana; Norina Forna (Romanian Journal of Medical and Dental Education)
Bone augmentation and sinus lift procedures are critical components of implant dentistry, particularly for patients experiencing insufficient bone volume in the maxilla due to tooth loss and maxillary sinus pneumatization. The integration of Plasma Rich in Growth Factors (PRGF) into these procedures has demonstrated substantial promise in enhancing bone regeneration and improving implant stability. This comprehensive literature review synthesizes findings from various studies and case reports to evaluate the efficacy, mechanisms, and clinical outcomes of using PRGF in these dental interventions.